Pengaruh Koneksi Politik, Corporate Social Responsibility, dan Good Corporate Governance terhadap Agresivitas Pajak (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Nurbaidah Mawarni; Sri Purwaningsih (Jaanur Elbarik Indonesia, 2025)
This study aims to determine the effect of Political Connections, Corporate Social Responsibility, and Good Corporate Governance on Tax Aggressiveness. The populations used on this research are from mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sample in this study amounted 24 companies observed over 5 years, resulting in a total sample size of 120 data points. The data were analyzed using SPSS version 26, adopting multiple linear regression as the analytical technique. The results of this study indicate that Political Connections does not has a significant effect on Tax Aggressiveness, while Corporate Social Responsibility has a positive effect on Tax Aggressiveness, and Good Corporate Governance also has a positive effect on Tax Aggressiveness.